International Year of Planet Earth 4. Utilizing Paleosols in Quaternary Climate Change Studies - Rutter, Nat (Geoscience Canada, 2009)
SUMMARY Paleosols are an important tool in interpreting Quaternary stratigraphic sequences. Buried, exhumed, and relict soils delineate ancient surfaces that may have undergone weathering processes for long periods. Soils, including many buried soils, sometimes manifest complex histories characterized by polygenetic or superimposed profiles. Identification of the type of paleosol, or at least a diagnostic horizon, can provide valuable insight into past climates, which in turn assists in determining past vegetation. Interpreting a paleosol may be hindered by eroded or partially preserved horizons, complex climatic and environmental histories, and in the case of buried paleosols, alteration of one or more soil horizons by infiltration of material from overlying units. Soil thickness allows the minimum time of the weathering interval to be estimated and various methods are available for estimating the age of a paleosol. Probably the most accurate dating technique involves bracketing the age of the pale-osol using datable material in sedimentary units above and below. Buried soils are found throughout the world, and are common in eolian deposits, such as loess and sand dunes, and allu-vial deposits. In Canada, and other glaciated regions, they are interbedded with glacial deposits and have been most useful in determining periods of sedimentary nondeposition, and interpreting interglacial climates. The loess– paleosol sequences of the Chinese Loess Plateau, where over 37 major climatic cycles have been identified in the past 2.6 Ma, are presented as an outstanding example of the usefulness of buried soils. The Chinese paleosols are similar to Canadian chernozems and Luvisols, indicating steppe–forest to dense forest or steppe–forest vegetation. The cycles are best explained by Milankovitch forcing.